Effect of dienogest on endometrial morphology and function with external genital endometriosis - A M Gerasimov; L V Kulida; N S Brykin; R N Gorta (IP Berlin A.V., 2014)
In this paper we investigate the effect of dienogest on endometrial morphology and function in patients with external genital endometriosis. It is shown that dienogest is effective in reducing pain in patients with external genital endometriosis and endometrial morphology and function improves, suppresses manifestations of inflammation in the lining of the uterus.